Associations between lower limb forces and cross punch force in elite male amateur boxers - Pádecký, J.; Kubový, P.; Brich, J.; Jebavý, R.; Tufano, J. (The Journal of Strength and Conditioning Research, 2021)
Although many different boxing punches exist, one of the most common is the straight cross. As with most punches, the lower limbs are said to heavily contribute to cross punch force, but previous research on the topic is contradictory, with some studies indicating a large role of the legs, while others indicate the opposite. Purpose: Therefore, the purpose of this study was to quantify lower limb forces and their association with cross peak force (PFCROSS). Methods: Twelve elite male amateur boxers (80.4 ± 11.1 kg, 181.6 ± 7.1 cm, 8.0 ± 5.9 years of boxing experience) participated in this study, which took place over 2 laboratory visits: familiarization and experimental. During the experimental visit, subjects completed a general warm up followed by a boxing-specific warm up. After 4 minutes of rest, subjects performed 1 maximal effort cross punch while standing on 2 3-axis force plates (Kistler group, Switzerland) in a self-selected stance. Subjects were instructed to punch the center of a separate tri-axial force plate that was suspended in the air at chin level (Kistler group, Switzerland). The sampling frequency of force plates was set at 12,000 Hz. Synchronized video recordings were used to identify the start of the punch using Qualisys Motion Tracking Manager (QTM) with a sampling frequency of 500 fps. All forces were transformed into relative forces (Newtons of force per kilogram of body mass). Standard multiple regression was used for 2 models separately, which included rear leg peak forces (PFRL) in the x, y, and z directions as independent variables for one model, and lead leg peak forces (PFLL) in the x, y and z directions as independent variables for the second model, both with PFCROSS as the dependent variable. Results: PFcross was 1.06 ± 0.19 N/kg, PFRL in x,y and z direction (0.14 ± 0.04 N/kg, -0.16 ± 0.18 N/kg, 0.72 ± 0.35 N/kg, respectively), PFLL in x, y and z direction (-0.40 ± 0.30 N/kg, 0.29 ± 0.18 N/kg, 1.03 ± 0.25 N/kg, respectively). Standard multiple regression model for PFRL resulted in R = 0.727, R2 = 0.528, and adjusted R2 = 0.351 with non-significant F change 0.096, while the model for PFLL resulted in R = 0.615, R2 = 0.378, and adjusted R2 = 0.145 with non-significant F change of 0.259. Standardized Beta coefficients, correlations, and collinearity statistics are present in Table 1. Conclusions: Peak leg forces explain about a half of a total variance (PFRL and PFLL adjusted R2, combined), indicating the importance of lower limb force production for the cross punch. The most explained variance from the legs is with PFRL in the x and z directions, with a lower explained variance with PFLL with similar results within x, y, and z directions. Practical Application: Strength and conditioning specialists should implement lower body exercises in vertical and lateral vectors in combination with rotational and upper body horizontal pushing exercises in order to increase cross punch force.